Socioeconomic status and obesity in adult populations of developing countries: a review - Carlos A. Monteiro; Erly C. Moura; Wolney L. Conde; Barry M. Popkin (The World Health Organization, 2004)
A landmark review of studies published prior to 1989 on socioeconomic status (SES) and obesity supported the view that obesity in the developing world would be essentially a disease of the socioeconomic elite. The present review, on studies conducted in adult populations from developing countries, published between 1989 and 2003, shows a different scenario for the relationship between SES and obesity. Although more studies are necessary to clarify the exact nature of this relationship, particularly among men, three main conclusions emerge from the studies reviewed: 1. Obesity in the developing world can no longer be considered solely a disease of groups with higher SES. 2. The burden of obesity in each developing country tends to shift towards the groups with lower SES as the country's gross national product (GNP) increases. 3. The shift of obesity towards women with low SES apparently occurs at an earlier stage of economic development than it does for men. The crossover to higher rates of obesity among women of low SES is found at a GNP per capita of about US$ 2500, the mid-point value for lower-middle-income economies. The results of this review reinforce the urgent need to: include obesity prevention as a relevant topic on the public health agenda in developing countries; improve the access of all social classes in these countries to reliable information on the determinants and consequences of obesity; and design and implement consistent public actions on the physical, economic, and sociocultural environment that make healthier choices concerning diet and physical activity feasible for all. A significant step in this direction was taken with the approval of the Global Strategy on Diet, Physical Activity and Health by the World Health Assembly in May 2004.